The 2022 World Cup and Migrants' Rights in Qatar: Racialised Labour Hierarchies and the Influence of Racial Capitalism. Issue 3 (12th July 2022) - Babar, Zahra; Vora, Neha
Abstract: Since winning the bid to host the 2022 World Cup, the Qatari government has channelled billions of dollars into infrastructural development to prepare for the tournament, which has ramped up the country's already high reliance on migrant labour. The international spotlight on migrant labour abuse has also become more intense as the date of the event approaches. Yet, human rights discourses surrounding World Cup 2022 continue to paint a simplistic and incomplete picture of migrant labour in the Gulf, where racism and its correctives are defined through the white gaze, with undercurrents of Orientalism and Islamophobia. In contrast, we offer a historical and transnational framework for understanding contemporary racialised labour and immigration systems in the Gulf. Effectively improving everyday life for migrant workers in the Gulf requires engaging both local stakeholders and the multiple actors and institutions—both inside and outside Qatar—involved in reproducing these systems.